1994
DOI: 10.1080/01635589409514338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fish oil on fatty acids and eicosanoids in metastasizing human breast cancer cells

Abstract: We examined the relationships between the suppressive effects of dietary fish oil on growth and metastasis of MDA-MB-435 human breast cancer cells in female nude mice and the primary tumor phospholipid fatty acid concentrations, phospholipase A2 activity, and eicosanoid levels. Mice (n = 120) were fed a 23% (wt/wt) corn oil (CO) linoleic acid (LA)-rich diet for seven days before and after 10(6) tumor cells were injected into a mammary fat pad, and then the mice receive one of three isocaloric diets containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…A risk factor associated with the etiology of breast cancer arises from animal and human epidemiology studies linking high dietary fat with increased incidence of breast cancer. Linoleic acid is the major polyunsaturated fatty acid consumed in the human diet and has been demonstrated to stimulate cell proliferation and metastasis in human breast carcinoma cells (38,39). Our investigation indicates that linoleic acid metabolism may play a central role in transduction of the EGF mitogenic signal from the cell surface to the nucleus and may provide a useful model for understanding neoplastic progression at a molecular level.…”
Section: Discussionmentioning
confidence: 95%
“…A risk factor associated with the etiology of breast cancer arises from animal and human epidemiology studies linking high dietary fat with increased incidence of breast cancer. Linoleic acid is the major polyunsaturated fatty acid consumed in the human diet and has been demonstrated to stimulate cell proliferation and metastasis in human breast carcinoma cells (38,39). Our investigation indicates that linoleic acid metabolism may play a central role in transduction of the EGF mitogenic signal from the cell surface to the nucleus and may provide a useful model for understanding neoplastic progression at a molecular level.…”
Section: Discussionmentioning
confidence: 95%
“…As early as 1994, Rose et al started a certain number of studies on the effects of dietary fish oil ω -3 PUFAs, including DHA, on the growth and metastases of MDA-MB-435 human breast cancer cells in female nude mice [82]. Animals were fed with three isocaloric diets containing 23% total fat but different proportion of corn oil (rich in linoleic acid-LA) and menhaden oil (rich in EPA and DHA) [65, 82].…”
Section: Dha As Adjuvant To Improve the Antimetastatic Efficacy Ofmentioning
confidence: 99%
“…Animals were fed with three isocaloric diets containing 23% total fat but different proportion of corn oil (rich in linoleic acid-LA) and menhaden oil (rich in EPA and DHA) [65, 82]. The authors reported that, in contrast to mice fed with diets rich in LA, mice receiving diets supplemented with EPA or DHA showed a significant suppression of both primary tumor growth rate and lung metastasis occurrence and severity, suggesting a role for EPA and DHA in the inhibition not only of tumor growth but also of metastasization of human breast cancer cells [82, 83]. Successively, the same authors investigated tumor responses to EPA or DHA administered immediately after surgical excision of the primary tumor (“postoperative adjuvant” activity).…”
Section: Dha As Adjuvant To Improve the Antimetastatic Efficacy Ofmentioning
confidence: 99%
“…For example, some researchers have suggested that soy products, because of their content of isoflavones such as genistein and daidzein, may be protective against breast and prostate cancers (47,48); there are limited data to support the hypothesis (49,50). Similarly, a high intake of the omega-3 polyunsaturated fats found in fish has been postulated to protect against cancer (51). Native Hawaiian men have the highest intake of fish and a relatively high intake of tofu, and their rate of prostate cancer is the lowest of the five ethnic groups.…”
Section: Author Manuscriptmentioning
confidence: 99%